Comparing Technical Proficiency of Elite Table Tennis Players with Intellectual Disability: Simulation Testing versus Game Play. Issue 2 (April 2014) - van Biesen, Debbie; Mactavish, Jennifer J.; Vanlandewijck, Yves C.
Technical skill proficiency among elite table tennis players with intellectual disabilities (ID) was investigated in this study using two approaches: an off-court simulation testing protocol and an on-court, standardized observational framework during game play. Participants included 24 players with ID ( M age = 25 yr., SD = 6; M IQ = 61, SD = 9), the top 16 performers, 13 men and 11 women, at the International Federation for sport for para-athletes with an intellectual disability (Inas) World Championships. Self-reported table tennis training experience of the players was 13 ± 5 yr. In the Simulation Testing condition, players were instructed to play five sets of basic and five sets of advanced skills, which were subsequently assessed by experts using a standardized and validated observational protocol. The same protocol was used to assess the same skills during Game Play. Ratings of overall technical proficiency were not significantly different between Simulation Testing and Game Play conditions. There was a strong positive correlation between technical proficiency measured during Game Play vs Simulation Testing for the variables flick, topspin forehand, and topspin backhand. No correlations were found for the variables contra, block, and push. Insight into this relationship is important for future development of classification systems for ID athletes in the Paralympic Games, because comparing competition observation with the athlete's potential shown during the classification session is essential information for classifiers to confirm the athlete's competition class.